Effect of phase noise on the optical millimeter-wave signal in the DWDM-RoF system - Mahmood, Rawa Muayad; Yaakob, Syamsuri; Ahmad, Faisul Arif; Ahmad Anas, Siti Barirah; Muhammad Zamzuri, Abdul Kadir; Che Beson, Mohd Rashidi (MDPI, 2022)
In this study, we examined the effect of phase noise on the optical millimeter-wave (mm-wave) signal in a dense wavelength division multiplexing radio-over-fiber (DWDM-RoF) system. A single modulator was used to generate the optical mm-wave signal in the DWDM-RoF system. This paper addresses the impact of phase noise, which results from phase imbalance, on the optical mm-wave signal. To lower the effect of phase noise on the optical mm-wave signal, the phase imbalance should be controlled. The phase imbalance can be controlled and decreased by adjusting the phase at the phase shift (PS). The system performance was analyzed using various parameters such as bit error rate (BER), signal-to-noise ratio (SNR), optical signal to noise ratio (OSNR), and error vector magnitude (EVM). From the results, we found the phase imbalance affected the optical mm-wave signal due to the imbalanced splitting of the signal intensity at the MZM. The phase imbalance impacts the phase noise, which impacts the optical mm-wave signal. The phase noise could be decreased by controlling the phase imbalance at the phase of 5π/12. The best results at the phase of 5π/12 were collected for phase noise at 0.02 degrees.